2022
DOI: 10.1186/s12902-022-00952-5
|View full text |Cite
|
Sign up to set email alerts
|

The relation between serum uric acid levels and diabetic peripheral neuropathy in type 2 diabetes in Guilan, north of Iran

Abstract: Background Diabetic peripheral neuropathy (DPN) is one of the most common chronic microvascular complications in type 2 diabetes mellitus (T2DM). Hence, the present study aimed to investigate the association between Serum Uric Acid (SUA) levels and diabetic peripheral polyneuropathy in patients with type 2 diabetes. Methods We performed this case–control study during 2019–2020 on individuals with diabetes referring to the Razi clinic of Rasht, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…Hyperuricemia was reported to be related to endothelial dysfunction and oxidative stress [ 31 , 32 ]. Our study showed that hyperuricemia was connected to an increased DPN risk, consistent with other studies [ 26 , 33 ]. Nevertheless, another cross-sectional study described a contrary relationship between large-nerve fiber dysfunction and UA levels in diabetic patients [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Hyperuricemia was reported to be related to endothelial dysfunction and oxidative stress [ 31 , 32 ]. Our study showed that hyperuricemia was connected to an increased DPN risk, consistent with other studies [ 26 , 33 ]. Nevertheless, another cross-sectional study described a contrary relationship between large-nerve fiber dysfunction and UA levels in diabetic patients [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…A higher cumulative incidence of DPN was observed in male than female patients in young adults [ 25 ]. However, another study with Iranian participants came to an opposite conclusion [ 26 ]. Numerous studies, including our research, indicated that T2DM patients with longer disease duration were more likely to develop DPN [ 9 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In study by Fayazi et al (17) , a total of 230 patients with type 2 diabetes were examined. The mean SUA level in the DPN group was significantly higher compared to DM without neuropathy (6.72 ± 1.75 vs. 4.57 ± 1.49 mg/dL).…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between DPN and SUA was mediated by several mechanisms which were reported by several studies. SUA serves as an antioxidant during the vascular passage, and on the contrary it has a reverse action in vascular smooth myocytes as it promotes the release and production of NO forming vascular impairment and DPN progression (17) . Some researchers have suggested that UA is closely related to DN that occurs shortly after hyperuricemia in patients with type 1 diabetes mellitus (T1DM), which can independently predict its occurrence (16) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation